A Gold Nanoparticle-based SERS Platform for Trace-Level Detection of Organic Contaminants in Municipal Tap Water - Cuong, Nguyen Kien (VNU Journal of Science: Natural Sciences and Technology, 2025)
Highly sensitive detection techniques are required because harmful organic residues in drinking water, such as dyes, antibiotics, and oils, pose significant health risks. We investigate surface-enhanced Raman scattering (SERS), which achieves sensitivity down to 10 -4 M, because Conventional Raman spectroscopy cannot reliably detect dye concentrations below 10 -9 M. Using sodium citrate as a reducing agent, we synthesized 10-20 nm gold nanoparticles from HauCl 4 ·3H 2 O and deposited them onto glass to create a 30-54 nm rough layer to create a SERS substrate. Raman signals are significantly amplified by this nanoscale roughness due to increased local electromagnetic fields. To evaluate the sensing performance of the substrate, Rhodamine 6G (Rh6G) solutions with concentrations from 10 -4 M to 10 -9 M were analyzed using a Raman spectrometer. Distinct spectral peaks of Rh6G were clearly observed even at 10 -9 M, whereas standard Raman spectroscopy on smooth glass failed to detect signals at comparable concentrations. This exceptional sensitivity results from strong localized surface plasmon resonance (LSPR) at hotspots in the ~30 nm thick gold nanoparticle film, where Rh6G signals were amplified several-fold. The substrate's substantial signal enhancement demonstrates its potential for detecting trace dye residues in drinking water using portable Raman spectrometers for convenient field deployment.